Temperatura i wilgotność powietrza w Ogrodzie Botanicznym UAM na tle wyników pomiarów stacji meteorologicznej Poznań Ławica - Łukasiewicz, Szymon (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2005)
The article presents temperature and humidity differentiation in the Adam Mickiewicz University (AMU) Botanical Garden in Poznań in comparison to a professional meteorological station, which is 3.5 k m away in the straight line. The conclusions make us change the methodology of taking measurements in park-andforest areas, which are botanical gardens, in comparison to standard climatic stations. The changes of atmosphere parameters caused by plants rely on: 1. The active surface, i.e. the surface on which light radiation is converted into thermal energy is the upper layer of tree and bush heads. This means shading under the heads and reducing the flow of solar energy to the ground surface. As a result, maximum temperatures are lowered at daytime (the largest amounts of heat are trapped in their heads), whereas at night, recorded minimum temperatures are higher in comparison to open areas: the foliage partially reflects long-wave radiation of the Earth. This effect mitigates daily temperature amplitudes in solid plant complexes. 2. Increased water supply from évapotranspiration processes, i.e. evaporation from the surface of the soil, watercourses, ponds, and its transpiration by plants result in higher air humidity. A larger amount of water vapor means a lower shortage of atmosphere humidity. This slows down unproductive plant evaporation in favor of productive transpiration. 3. Filling the space with trees, bushes, climbing plants, cover plants, etc. is a considerable obstacle for the wind, thus decreasing its strength. A s a result, instead of a free air flow taking moisture particles, natural obstacles decrease wind velocity within the plant complex and force its turbulence. This results in a longer stay of the humid air mass in the area of the garden, and therefore, lower sucking force of the atmosphere depending on wind velocity, in respect to humidity. 4. While raining, the moistened surface is unproportionally larger (up to over 10 times) than the area; this is the leaf surface of subsequent plant floors. After raining, evaporation from such a large surface results in higher air humidity, in comparison to the area without trees. Simultaneously, due to decreasing wind power, water vapor saturation of air after rains is maintained longer in comparison to observations in other areas, including the climatic station of the Meteorological Institute (IMGW).